STRATEGI PENGELOLAAN FACEBOOK ANTVLOVERS DALAM MEMBANGUN AUDIENCE ENGAGEMENT - Riyadh Jordan (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2020)
The phenomenon to be discussed in this research is social media with various features allowed audiences from a television program to contribute to promote and stimulate the television program growth in a certain television station. ANTV as one of the private television stations in Indonesia is to take advantage of it to build engagement with audiences that become the social media users, with ANTVLovers that become the official Facebook account for uploading their content from the on-air program. Seeing the trend of using social media and started to have a big role in the television industry, the writer aims to find out what is the strategy to develop ANTVLovers Facebook account to build audience engagement. The concept that uses in this research is how to build engagement with social media stated by Dave Evans. The paradigm that will use in this research is constructivist by using a descriptive qualitative approach. The method in this research is a study case with the source of data from the key informan is Social Media Creative, the primary informan is Senior Marketing Communication Manager ANTV, the supportive informan is Staff Creative ANTV. This study uses the participative observation, in-depth interview, and documentation study for the data collection technique. The conclusion from this research is the result of using the strategy to develop ANTVLovers Facebook account to build audience engagement rated as a successful strategy because we could see the performance during the period May 1, 2019, until February 4, 2020.Keywords: Strategy, Social Media, Audience Engagement